Development of Mobile Learning for Distance Learning in Procurement Logistics Course (Case Study: Logistic Engineering Student Program UPI) - Aulia Zikri Rahman; Hizba Muhammad Sadida; Hanissa Okitasari; Galuh Chisyti Nur Fadhilah (Journal of Logistics and Supply Chain, 2021)
Logistics Engineering study program students are required to take several Core Expertise Courses at the Study Program, including among the list is logistics procurement courses. This subject is compulsory in the logistic science cluster because in a unified process of downstream goods in the logistics process cannot be separated from the role of procurement. In this course students will learn about how the procurement process takes place in a complete logistics cycle, but the complexity for this course is high enough that an alternative is needed that can be used as supporting student learning. With advances in information technology, existing learning methods can be enhanced to produce maximum and measurable output through indicators. This study aims to design and develop an independent learning mobile application for logistics procurement courses targeting students of the UPI Logistics Engineering study program. The first development step is to design and adopt this learning process into the application. The research was conducted with the intention of utilizing context-awareness computing to provide material personalization for each user and evaluation in the form of a quiz. In the final stage of research, the application made will be tested to determine the level of usability that will be applied in lectures. The expected result is a robust system and is expected to support blended learning to increase students' interest and understanding of logistics procurement courses.